Stroke after spontaneous intracranial hypotension: Not a single mechanism. Case report and review of literature. (April 2020) - Redon, Sylvain; Laksiri, Nadia; Doche, Emilie; Hirtz, Chloé; Brun, Gilles; Donnet, Anne
Highlights: Brain infarction is a rare complication of spontaneous intracranial hypotension (SIH). The main mechanism is the stretching of arteries due to the sagging of the brain. The presence of a patent foramen ovale in SIH cases is a risk factor for stroke. Abstract: Spontaneous intracranial hypotension (SIH) is a rare syndrome, typically manifests as orthostatic headache. Sometimes considered as benign illness, neurological complications are well described, in particular subdural hematoma and cerebral venous sinus thrombosis. Brain infarction as complication of SIH is rarely reported. The main mechanism supported in the literature is the stretching of arteries due to the sagging of the brain. We report a case of SIH followed with brain infarction, with a distinct presentation from previous literature, suggesting a different mechanism. A 35 year-old had severe orthostatic headache, responsible for prolonged bed rest. One month later, he had acute left hemiparesis secondary to stroke and right posterior cerebral artery occlusion. Stroke MRI showed arguments for intracranial hypotension (thickened meninges). He was successfully treated with intravenous rtPA thrombolysis. Headache were resolved after an epidural blood patch. A patent foramen ovale was detected. Clinical features of this description were compared with previous literature. This case suggest a different mechanism for cerebral infarction after intracranial hypotension. In case of prolonged lying down due to intracranial hypotension, the presence of patent foramen ovale could be a risk factor for embolic stroke.